The effect of customer and supplier concentrations on firm resilience during the COVID‐19 pandemic: Resource dependence and power balancing. Issue 3 (24th January 2023) - Jiang, Shenyang; Yeung, Andy C. L.; Han, Zhaojun; Huo, Baofeng
Abstract: The COVID‐19 pandemic has created significant disruptions in both demand and supply. Our study makes use of such dramatic changes in demand and supply during the pandemic to examine resource dependence and power balancing/unbalancing issues in buyer–supplier relationships. Specifically, we investigate the effect of customer and supplier concentrations on firm resilience during the pandemic. Drawing on resource‐dependence theory (RDT), we theorize that shifts in demand and supply in different pandemic stages influence the effect of customer and supplier concentrations on firm resilience by altering the power dynamics between focal firms and their concentrated customers and suppliers. Central to our theorizing is that the worsening power imbalance is more detrimental. Measuring firm resilience by loss and recovery (i.e., change) in productivity, our analysis of 23, 440 Chinese listed firms' quarter observations from 2019 to 2020 shows that customer concentration is negatively related to firm resilience in the disruption stage but has no effect in the restoration stage. Supplier concentration is positively related to firm resilience in the disruption stage but undermines firm resilience in the restoration stage. These findings largely confirm our theoretical propositions. We discuss the theoretical and managerial implications. Highlights: Customer and supplier concentrations are important supply chain characteristics that influence firm resilience during a crisis. Their effects are different across different stages of the pandemic. Customer and supplier concentrations become more detrimental when power imbalance is worsened; thus, firms should try to balance the power relationships with their concentrated customers and suppliers in order to benefit more from customer and supplier concentrations. Firms should be aware that the macro demand and supply shifts induced by a crisis may change the resource dependence and power dynamics in buyer–supplier relationships, which in turn affect the efficacy of resilience strategies.